S112 Neural respiratory drive as a surrogate marker of chronic lung allograft dysfunction. (December 2018) - Kaltsakas, G; Patout, M; Arbane, G; Shah, NM; Soresi, S; Hart, N; Marino, P; Simon, A; Carby, M; Reed, A; Lhuillier, E; Murphy, PB
Abstract : Chronic lung allograft dysfunction (CLAD) is the main complication following lung transplantation and remains the most common limitation of long-term survival. CLAD is a descriptive term and is defined by a persistent reduction (>10%) in FEV1 and/or FVC from the best post-transplant baseline. The aim of this study was to assess the predictive ability of respiratory function tests other than spirometry and static lung volume assessment in the diagnosis of CLAD. Patients following bilateral lung transplantation were prospectively studied between July 2016 and March 2017. Patients included were clinically stable and transplanted at least six months prior to enrolment. Respiratory muscle function was assessed with the maximum static expiratory (Pemax) and inspiratory (Pimax) mouth pressures, and the maximal sniff nasal inspiratory pressure (SNIP). The electromyography of the parasternal intercostals (EMGpara) was recorded whilst the subject was self-ventilating at rest in semi-recumbent position. EMGpara%max was calculated as the mean of EMGpara divided by the maximum EMGpara × 100% and the neural respiratory drive index (NRDI) was obtained from EMGpara%max × respiratory rate. Chronic dyspnoea was assessed by the Medical Research Council (MRC) scale. Forty patients (17 males) were included in the study with age of 52±12 years. Time since lung transplantation was 11.6±8.3 years. The MRC was 2 (1, 3). Twenty-one (53%) patients had CLAD. CLAD patients had a significantly higher EMGpara%max and NRDI and a significantly lower respiratory muscle strength than those without CLAD (table 1). Following bronchodilation, EMGpara%max decreased by −1.8% (95%CI −2.8% to −0.8%; p<0.001) as compared to baseline without significant difference between CLAD and no CLAD patients. Using a cut-off value of EMGpara%max ≥9%, EMGpara%max had a sensitivity, specificity, positive predictive value and negative predictive value of: 90%, 48%, 63% and 36% respectively to diagnose CLAD (AUC=0.692, p=0.038). The MRC was related to EMGpara%max, NRDI, Pimax, and FEV1 (r=0.457 p=0.005; r=0.607 p<0.001; r=0.627 p<0.001; r=−0.674 p<0.001, respectively). In conclusion, CLAD patients have higher neural respiratory drive and impaired respiratory muscle strength. The measurement of respiratory drive may enable identification of patients at risk of developing CLAD leading to earlier intervention in order to prevent the onset of CLAD.